Exploring ligand-protein interaction: A laboratory exercise on herbicide binding to plasma transport protein - Roslan, Amira Adlin; Tayyab, Saad (Wiley, 2019)
A laboratory exercise on the interaction between the herbicide pendimethalin (PM) and goat serum albumin (GSA), a carrier protein present in mammalian blood circulation, is described. Fluorescence spectroscopy was used to study the binding reaction between PM and GSA. Titration of a constant amount of the protein (GSA) with increasing ligand (PM) concentrations produced a consecutive decrease in the protein's fluorescence. Treatment of the fluorescence quenching data according to the Stern–Volmer equation yielded the values of the Stern–Volmer constant (K sv ) and bimolecular quenching rate constant (k q ), whereas values of the binding constant (K a ) and number of binding sites (n) were obtained from the double logarithmic plot. This experiment provides an exciting opportunity for undergraduate students to independently perform ligand binding studies with a protein, in addition to providing the means for the determination of their binding parameters. © 2019 International Union of Biochemistry and Molecular Biology, 47(2): 156–160, 2019. © 2019 International Union of Biochemistry and Molecular Biology